2018
DOI: 10.1007/s11145-018-9859-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring individual and gender differences in early writing performance

Abstract: Boys' relatively poor progress in writing development is of particular concern in education with both cognitive and social factors proposed as possible accounts of this discrepancy. This study examined whether differences in cognitive skills such as handwriting and spelling or phonological processing abilities could explain gender differences in early writing. An opportunity sample of 116 children (52 male) ranging in age from 5:0 to 6:7 years were recruited from six UK schools. Tasks assessing vocabulary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 125 publications
(164 reference statements)
3
25
3
3
Order By: Relevance
“…However, to our knowledge, previous studies have not yet addressed potential interaction effects of gender with intervention programs and the stability of changes over time, while other aspects of gender differences on writing (i.e., text quality, processes of planning and text structure) are well-documented [43]. For example, gender differences attest that 15%-19% fewer boys than girls achieve the expected standards of writing on leaving UK primary schools aged 11 years [44], consistent with other studies reporting a female advantage in writing [45,46]. Girls perform better than boys in spelling, writing essays and sentence composition measured on the Wechsler Individual Achievement Test-Third Edition [47], with a gap increasing with age during the school years [48].…”
Section: Intervention Programs Duration and Gender Differencesmentioning
confidence: 99%
“…However, to our knowledge, previous studies have not yet addressed potential interaction effects of gender with intervention programs and the stability of changes over time, while other aspects of gender differences on writing (i.e., text quality, processes of planning and text structure) are well-documented [43]. For example, gender differences attest that 15%-19% fewer boys than girls achieve the expected standards of writing on leaving UK primary schools aged 11 years [44], consistent with other studies reporting a female advantage in writing [45,46]. Girls perform better than boys in spelling, writing essays and sentence composition measured on the Wechsler Individual Achievement Test-Third Edition [47], with a gap increasing with age during the school years [48].…”
Section: Intervention Programs Duration and Gender Differencesmentioning
confidence: 99%
“…Previous research shows various results regarding gender differences in writing. In some studies gender differences in written text quality have been found (Adams & Simmons, 2018;Bourke & Adams, 2011). For example, in Adams and Simmons, girls performed significantly better than boys did in written text composition, but not in transcription skills such as spelling and handwriting fluency.…”
Section: Gender Differencesmentioning
confidence: 99%
“…It was further expected that girls would outperform boys in text length and written narrative text quality, as some of the previous research shows evidence that girls write longer texts with better text quality compared with boys (cf. Adams & Simmons, 2018;Williams & Larkin, 2013). In addition, lowproficiency students were expected to gain more from participating in the experimental group using Joint Construction compared with students of high proficiency level (cf.…”
Section: Purposementioning
confidence: 99%
“…The absence of a relationship with text spelling may appear to be at odds with this account. However, there is evidence that spelling individual words to dictation may be reliant upon different cognitive processes than those supporting spelling accuracy during text construction (Adams & Simmons, 2019;Harrison et al, 2016). The lack of a relationship between meaning-related aspects of the HLE and sentence and text level writing was unexpected given associations between such experiences and skills underpinning reading comprehension (Hood et al, 2008;Manolitsis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%